Analisis Dan Rancang Bangun Prototype Web Marketplace UMKM Juara - Munir, Sirojul; Aufah, Anifatul; Septiani, Kuati; Fauziah, Syifa Tazkiy (Jurnal Teknologi Terpadu, 2020)
Small and medium-sized enterprises (SMEs) have an essential role in Indonesia's economy, especially in West Java. However, some problems make it difficult for SMEs in West Java to progress, namely the availability of raw materials, management, and marketing. The West Java Government created the UMKM Juara program to help the growth and development of SMEs. In this research, a web-based information system was developed using ReactJS and NodeJs to support the UMKM Juara program by focusing on the marketplace, preordering, and coaching and regulation modules. The Scrum method is used for application development combined with the use of UML diagrams for design documentation. The BlackBox testing results obtained 92%, 75%, and 80% for each marketplace module, preorder, and regulatory guidance.Â In comparison, users with the User Acceptance Test method obtained results with user acceptance rates of 77.33%, 76%, and 86.2%. It can be concluded that the web marketplace application prototype is feasible to use. Still, it needs improvement and development to improve the application.